The effects of four different solvent vapours on the restoration of obliterated stamp markings from five different wooden surfaces. Issue 3 (May 2023) - Uysal, Serdar; Yildiz, Emrecan; Armutcu, Canan; Sarıbey, Aylin Yalçın; Uzun, Lokman
Highlights: One of the rare researches about the restoration of defaced characters on wooden surfaces. Pioneering use of different types of wooden surfaces for forensic marks examination. Easy, rapid, and cost-effective recovery of scraped characters on wooden surfaces. Possible on-site method for restoration of the marks on wooden surfaces. Abstract: The stamp markings on wooden surfaces, which are placed on trees and products including antiques, indicate the status of trees and involve identifying data regarding the products. Such markings are obliterated either to facilitate illegal logging or to conceal product information. Despite the wide literature on the restoration of obliterated characters on metal and polymer surfaces, the recovery of defaced characters on wooden surfaces appears to be understudied. Several reference texts in the forensic marks' examination literature suggest that water, water vapor, and alkaline solutions are useful in restoring the abraded markings on the wood. Since there does not seem to be any experimental study proving such success, this study aimed to fill this gap. This study conducted experimental research by using water, ethanol, ammonia, and chloroform to recover the scraped characters on samples obtained from walnut, beech, spruce, oak, and cedar trees. The cold-stamped characters, which were defaced at varying depths, were restored using vapor and liquid phases of four solvents. While the vapor phases of water, ethanol, and ammonia yielded good outcomes on all types of wooden surfaces, the liquid phases did not seem to be useful in the revisualization process. The response of the vapors, which varied between 62 and 220 s, depended on the type of wood. The restoration technique developed in this research offers the possibility of on-site usage, easy application, utilization of low-cost solvents, rapid recovery, and effectiveness on various wooden surfaces. Overall, the restoration methodology used in this research appears to be fruitful in retrieving identifying information on wooden samples.